1999
DOI: 10.1007/s003300050861
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of transabdominal ultrasonography in detection of intraperitoneal fluid in humans

Abstract: The sensitivity and specificity of ultrasonography in detection of free intraperitoneal fluid is over 90 %. The lowest detectable volume of free fluid in humans is unknown. The distribution of intraperitoneal fluid was studied in 86 patients by transabdominal US in group A (n = 21, 10 ml of fluid), in group B (n = 15, 50 ml of fluid) and group C (n = 50, splenic trauma). Ultrasound detected fluid in 15 of 21 patients in group A, and in all patients in groups B and C. In group A 10 ml of fluid was found in 71 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 20 publications
0
26
0
3
Order By: Relevance
“…The acoustic window created by a full bladder enhances detection of fluid in the pelvis [18]. It is not until there are larger intraperitoneal fluid volumes (>500 mL) that fluid is detectable in the perihepatic and perisplenic spaces [31]. A study by Abrams and colleagues [32] confirmed these findings and, further, determined that 5( of Trendelenberg positioning resulted in the detection of free fluid in Morison's pouch (668 mL in the supine position and 443 mL in Trendelenberg's position).…”
Section: Fluid Volume and Scoring Systemsmentioning
confidence: 99%
“…The acoustic window created by a full bladder enhances detection of fluid in the pelvis [18]. It is not until there are larger intraperitoneal fluid volumes (>500 mL) that fluid is detectable in the perihepatic and perisplenic spaces [31]. A study by Abrams and colleagues [32] confirmed these findings and, further, determined that 5( of Trendelenberg positioning resulted in the detection of free fluid in Morison's pouch (668 mL in the supine position and 443 mL in Trendelenberg's position).…”
Section: Fluid Volume and Scoring Systemsmentioning
confidence: 99%
“…Der FAST-Ultraschall ist Bestandteil nationaler und internationaler Leitlinien[1,2]. Obwohl durch den Einsatz moderner Ultraschallgeräte bereits geringe Flüssigkeitsansammlungen detektiert werden können[3], weist die vielfach untersuchte Sensitivität des initialen Ultraschalls zum Nachweis von Organverletzungen und freier Flüssigkeit eine weite Bandbreite von 0,44 -0,88 auf[4 -6]. Neben der initialen Diagnostik kommen Ultraschalluntersuchungen gemäß der Leitlinie der Deutschen Gesellschaft für Unfallchirurgie als Bestandteil des Behandlungsalgorithmus für die weitere klinische Verlaufsbeurteilung polytraumatisierter Patienten vielfach zum Einsatz[1].…”
unclassified
“…This case could be considered traumatic, although the injury was iatrogenic. Ultrasound has good sensitivity for intraperitoneal fluid, detecting as little as 10 -50 cc in the pelvis on transvaginal examination, although more fluid (typically about 250 cc) is needed for a positive finding in Morison's pouch, with sensitivity increasing dramatically at volumes above 500 cc (17,18). An earlier transvaginal ultrasound may have picked up evidence of fluid in the pelvis, although a small amount of pelvic fluid may be physiologic, or normal after a pelvic operation.…”
Section: Discussionmentioning
confidence: 94%